2022
DOI: 10.1093/ptj/pzac051
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Personalized Outcomes Forecasts on Clinical Reasoning of Physical Therapists in Intermittent Claudication: A Vignette Study

Abstract: Objective Guidelines recommend supervised exercise therapy and lifestyle counseling by a physical therapist as initial treatment of patients with intermittent claudication. However, guidelines provide only a crude estimate of the outcomes that therapists and patients might expect from treatment. The purpose of this study was to explore the impact of personalized outcomes forecasts (POFs) on the decision-making process of physical therapists and to learn lessons on facilitating the use of fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 34 publications
(47 reference statements)
3
16
0
Order By: Relevance
“…One source defines it as "walking induced discomfort and pain in the hip and leg muscles that typically disappears after a brief rest"; IC is considered a prevalent sign of peripheral arterial disease. [236] The treated group had a lower ulceration rate than the other group, which showed no signs of IC and did not get the cilostazol treatment. [235] Cilostazol prevents platelet aggregation.…”
Section: Influence Of Formulations Administrated Systematically or Th...mentioning
confidence: 79%
“…One source defines it as "walking induced discomfort and pain in the hip and leg muscles that typically disappears after a brief rest"; IC is considered a prevalent sign of peripheral arterial disease. [236] The treated group had a lower ulceration rate than the other group, which showed no signs of IC and did not get the cilostazol treatment. [235] Cilostazol prevents platelet aggregation.…”
Section: Influence Of Formulations Administrated Systematically or Th...mentioning
confidence: 79%
“…Similarly, in Sinnige et al's study, therapists perceived that providing patients with personalized recovery information could motivate patients to achieve therapy goals or could demotivate patients with a poor prognosis. 13 Some therapists from their study indicated they wouldn't provide personalized recovery information to individuals who were performing below predicted measurements. 13 Sinnige et al discussed that withholding information from patients because of a poor prognosis may be problematic given patients' right to know about their health, yet they also acknowledged that the use of clinical tools are often up to the discretion of clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…12 PTs can use these predictions to (1) help patients set realistic expectations about their recovery, (2) prospectively monitor patients' recovery against their predicted recovery to inform personalized treatment decisions, and (3) provide patients with feedback about their recovery to reduce postoperative anxiety and uncertainty. 13 The tool can be used similarly to childhood growth charts, which parents and pediatricians use to monitor and set expectations about a child's growth over time.…”
Section: Introductionmentioning
confidence: 99%
“…The POFs were implemented among physical and exercise therapists affiliated with ‘Chronic CareNet’, a Dutch nationwide network of specialised therapists providing community-based SET and lifestyle counselling to patients with non-communicable diseases like intermittent claudication 34. The study was conducted in the Netherlands from August 2019 to November 2021 (‘Netherlands Trial Register’ number: NL8838), and the study protocol has been described previously 35. The RECORD checklist was used as a guide in the reporting of this study 36…”
Section: Methodsmentioning
confidence: 99%
“…By informing patients of the expected course and outcome of therapy, POFs may help therapists to tailor care to the needs of the individual and thereby potentially improve patient outcomes 25. Moreover, we expect that POFs could enable therapists to improve patient engagement and shared decision-making (SDM) 21 26. The latter is noteworthy since the use of SDM is limited among physical therapists while it is considered a cornerstone of personalised care 27–31…”
Section: Introductionmentioning
confidence: 99%